MARKETING STRATEGY ENTREPRENEUR BASED OF PT. GILI ENCHANTING PROSPERITY THROUGH THE NORTH LOMBOK TOURISM INDUSTRY - Samsudin Samsudin; Didin Hadi Saputra (UNIVERSITAS INDRAPRASTA PGRI, 2020)
This qualitative descriptive study aims to describe the marketing strategy of PT. Gili Pesona Sejahtera in increasing revenue through the tourism industry in Gili Trawangan, Regency of Winner, Regency of North Lombok in 2018. with PT. Gili's Persona Sejahtera as respondent Data collection uses observation, interview, and documentation methods. Data analysis techniques using the Miles and Huberman models which include data reduction, data presentation (data display), and verification (concluding). the results showed that the marketing strategy of PT. Gili Pesona Sejahtera in its operations collaborates with accommodation entrepreneurs including hoteliers, travel agent entrepreneurs, water entrepreneurs, internet marketing entrepreneurs, and offline space guides. PT. Gili Pesona Sejahtera implements a mutually beneficial partnership in the form of providing a fee of 10% of the total selling price of rooms with partners who are able to lobby travelers